Dependence of Oil and Gas Production Rate on the Formation Structure (Czech Journal of Multidisciplinary Innovations, 2023)
In most cases, oil production occurs when it is replaced in the pore space of a productive formation with water or gas, both under natural operating conditions and with artificial methods of maintaining reservoir pressure by flooding or gas injection.